Evaluating the bioactive effects of flavonoid hesperidin: A new literature data survey - Kuntić Vesna; Brborić Jasmina; Holclajtner-Antunović Ivanka; Uskoković-Marković Snežana (Vojnosanitetski Pregled, 2014)
nema